Denmark Strait during the Late Glacial Maximum and marine isotope stage 3: sediment sources and transport processes - Andrews, J. T. (2019)
The sediment records from north and south of Denmark Strait (cores PS2644 and MD99-2323) and on the Kangerlussuaq Trough Mouth Fan (KTMF) (MD99-2260) are evaluated for the period 12 to 60 cal ka BP with the goal of evaluating: 1) the relative roles of the Greenland and Iceland Ice Sheets in sediment composition, 2) the processes of sediment supply, and 3) the relationship, if any, between the atmospheric derived ice core records and glacial marine sediment history. These questions were addressed using counts of coarse (> 2 mm) ice rafted debris (IRD), magnetic susceptibility, grain-size spectra, and sediment mineral composition. A significant difference in these variables occurred between MS3 and IVII52, with the latter showing small to modest abrupt changes in felsic and mafic minerals and in IRD, compared to larger and less variable changes during MIS2. The dominant bedrock source archived in the cores is the Cenozoic basaltic outcrops from East Greenland and Iceland (-60%) but there are frequent pulses of felsic-rich sediments (similar to 17-36%), which coincided with Greenland stadials. There is also a persistent detrital carbonate input. The largest shift in most sediment proxies occurred 28-30 cal ka BP reflecting the sustained expansion of the ice sheets. The grain-size spectra on the Snorri Drift (MD99-2323) reflected complex depositional histories involving the supply of poorly sorted glacially derived sediment (sand, silt, and clay) and reworking by bottom currents.